Enterprise messaging with JMS : advanced topics and Spring JMS - Richards, Mark; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2014)
"Dive into advanced topics for using Java Message Service (JMS) in the enterprise with this comprehensive video course. Through live, interactive coding in both JMS 1.1 and JMS 2.0, messaging expert Mark Richards take you deep into several advanced JMS features and techniques, including JMS transaction management, embedded messaging, RESTful JMS, Spring JMS, and message streaming. If you're a Java developer who understands JMS basics, particularly though Mark Richards' introductory video-Enterprise Messaging Using JMS: Fundamentals-this advanced course is the ideal way to continue your journey through enterprise messaging. Topics include: Design techniques and common message design pitfalls; How and when to use transactions with messaging; Using an embedded message broker in your application; Creating self-healing and auditing systems using message browsing; Techniques for sending and receiving large documents and images in messages; Sending and receiving messages through HTTP with RESTful JMS; Techniques for making your messaging applications run faster and scale better; Using Spring JMS to send and receive messages in Spring-based applications; Harnessing the full power of Spring JMS with Message Driven POJOs."--Resource description page.
Title from title screen (viewed November 17, 2014).
Presenter, Mark Richards.
Keywords: Java; Telecommunication -- Message processing; Electronic books